2021
DOI: 10.3390/ma14195726
|View full text |Cite
|
Sign up to set email alerts
|

An Aggregation-Free Local Volume Fraction Formulation for Topological Design of Porous Structure

Abstract: Cellular structure can possess superior mechanical properties and low density simultaneously. Additive manufacturing has experienced substantial progress in the past decades, which promotes the popularity of such bone-like structure. This paper proposes a methodology on the topological design of porous structure. For the typical technologies such as the p-norm aggregation and implicit porosity control, the violation of the maximum local volume constraint is inevitable. To this end, the primary optimization pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Later, Giraldo-Londono et al generalized the AL technique for the transient topology optimization issue by including stress constraints at each time step [128]. An aggregation-free local volume proportion formulation for porous structure was presented by Long et al [129], which was subsequently developed into a multimaterial porous structure [130]. The AL method is also performed to the topology optimization under constraints of multiple nodal displacements, maximum transient responses problem, and fatigueresistance issue [131][132][133].…”
Section: Augmented Lagrangementioning
confidence: 99%
“…Later, Giraldo-Londono et al generalized the AL technique for the transient topology optimization issue by including stress constraints at each time step [128]. An aggregation-free local volume proportion formulation for porous structure was presented by Long et al [129], which was subsequently developed into a multimaterial porous structure [130]. The AL method is also performed to the topology optimization under constraints of multiple nodal displacements, maximum transient responses problem, and fatigueresistance issue [131][132][133].…”
Section: Augmented Lagrangementioning
confidence: 99%
“…Dou [33] imposed implicit control over local volume proportion via morphology transformation mode, which was extended to the thermo-mechanical buckling problem [34]. Long et al [35,36] recently suggested a cluster-free formulation for the local volume constraints to verify that the upper bounds can be satisfied precisely. Hu et al [37] introduced the block-wise similarity constraints into the generative design by mimicking textures.…”
Section: Topology Optimization On Porous Structuresmentioning
confidence: 99%
“…Therefore, the penalty parameter p should be greater than 1 (p > 1) in penalized SEMDOT for convergency and reasonable topologies. The porous structure design problem is a suitable test case to evaluate the capability of SEMDOT in the aspect of forming smooth boundaries as numerous holes will be formed in this case [72,73]. Here, the porous structure constraint proposed by Wu et al [72] is incorporated into Equation ( 26), which is formulated by…”
Section: Compliance Minimization Casementioning
confidence: 99%